Relevansi Peraturan Dalam Mendukung Praktek Profesi Apoteker Di Apotek - Hartini, Yustina Sri (Majalah Ilmu Kefarmasian, 2009)
One of pharmacy’s duty is being the place of pharmacist to serve patient profesionally. The fact, it was many report in mass media that pharmacist ‘s performance is not good enough. Many pharmacy regulation already issued, this review report and discuss pharmacy regulations related to pharmacy. Regulation that have issued by goverment about pharmacy ie: St. No.419 in 1949, Goverment regulations (PP) No.25 in 1980, Rule of Minister of Health (Permenkes) No.26 in 1981, Kepmenkes No. 278, 279 and 280 in 1981, Permenkes No.240 in 1990, Kepmenkes No.347 in 1990, Permenkes No.922 in 1993, Act (UU) No.5 in 1997, UU No.22 in 1997, PP No.72 in 1998, UU No.8 in 1999, Kepmenkes No.1332 in 2002, UU No.29 in 2004, Kepmenkes No.1027 in 2004, and Permenkes No.384 in 2007. Pharmacy regulations are enouh and relevance to support pharmacist practice, commitment to adhere the regulations and enforcement its implementation still required.